Determinants of Anemia among Children Aged 6-59 Months in Ethiopia: Further Analysis of the 2016 Ethiopian Demographic Health Survey - Melash Belachew Asresie; Gedefaw Abeje Fekadu; Gizachew Worku Dagnew (Hindawi Limited, 2020)
Background. Anemia among children is a global public health problem. The burden is high in developing countries including Ethiopia. Although there are some studies about anemia among children, there is a dearth of information about factors associated with anemia in Ethiopia. Therefore, this analysis was performed to identify factors associated with anemia among children aged 6-59 months in Ethiopia. Methods. We used the 2016 Ethiopian Demography and Health Survey (EDHS) data. EDHS was a community-based, cross-sectional study conducted from January 18, 2016 to June 27, 2016. The 2016 EDHS selected the participants using a two-stage stratified cluster sampling technique. A total of 8,462 children aged 6-59 months were included for this analysis. Both descriptive and logistic regression analyses were performed using Stata version14. A P value less than 0.05 at 95% confidence interval was set to test the statistical significance. Results. The analysis indicated that about 58% (95% CI: 55.1, 60.1) of children aged 6-59 months were anemic. Of those, 29.4% and 3.1% had moderate and severe anemia, respectively. The analysis revealed that stunted (AOR = 0.135, 95% CI: 1.13, 1.62) and underweight (AOR = 1.27, 95% CI: 1.04, 1.55) children had higher odds of being anemic. Besides, children aged 6-23 months (AOR = 1.39, 95% CI: 1.06, 1.82), 24-42 months of age (AOR = 1.26, 95% CI: 1.05, 1.51), and those with fever (AOR = 1.34, 95% CI: 1.07, 1.67) had higher odds of being anemic. Similarly, children from anemic mothers (AOR = 1.86, 95% CI: 1.58, 2.18) and poor households (AOR = 1.35, 95% CI: 1.09, 1.67) were at a higher risk of anemia. Children from households with large family sizes (AOR = 1.29, 95% CI: 1.03, 1.60), young mothers (15-24 years of age (AOR = 1.39, 95% CI: 1.06, 1.82) and 25-34 years of age (AOR = 1.26, 95% CI: 1.05, 1.51)), and developing regions (AOR = 1.44, 95% CI: 1.03, 2.02) also had higher odds of developing anemia. Conclusion. The overall prevalence of anemia among children aged 6-59 months in Ethiopia was high. Malnourished children (stunting and underweight); children with fever; children from anemic, uneducated, and young mothers; and children from large and poor families had higher odds to develop anemia. Therefore, preventing childhood illnesses and maternal anemia should be strengthened to reduce anemia among children.